Angiotensin-converting enzyme inhibition activity and LCMS analysis of Syzygium polyanthum (Wight) Walp leaves - Tuan Anuar, Tuan Ashraf Faiz; Ismail, Azlini; Omar, Muhammad Nor; Mohamed Suffian, Izzat Fahimuddin; Abdul Hamid, Azzmer Azzar (Pusat Pengajian Sains Kesihatan, 2021)
Syzygium polyanthum is an ethnomedicinal plant that is widely used among the Malay community for treating hypertension. Previous studies have shown that the plant leaves have a significant antihypertensive effect in rats; however, its mechanism of action and the bioactive compounds is not yet well-studied. One of the possible mechanisms to reduce blood pressure is through inhibiting the angiotensin-converting enzyme (ACE). Therefore, this study aims to determine the ACE inhibitory activity of S. polyanthum leaves and its phytochemical composition. S. polyanthum leaves were dried, ground, macerated with water in a bath-sonicator, and then freeze-dried to produce the aqueous S. polyanthum (ASP) leaves extract. The ACE inhibition activity of ASP was tested using Cushman and Cheung method at a range of concentrations from 1 to 1000 µg/ml. The phytochemical composition in ASP was then analysed using Liquid Chromatography Quadrupole Time-of-Flight Mass Spectrometry (LCQTOF/MS). It was found that the concentration of ASP that causes 50 % of ACE inhibition activity (IC50) was 41 μg/ml. Through LC-QTOF/MS analysis, there were 26 compounds identified in ASP with the following major compounds; 1-galloyl-glucose (21%), feroxin A (12%), nilocitin (10 %), 2,6-di-O-galloyl-β-D-glucose (9%), 1-O-galloylpedun-culagin (7%), 5-desgalloylstachyurin (6 %), and yakuchinone A (6 %). In conclusion, this study showed that ASP which majorly consists of 1-galloyl glucose exhibited significant ACE inhibitory activity. Further bioassay-guided isolation is required to determine whether 1-galloyl glucose is the potential bioactive compound responsible for this activity.